PENERAPAN CONTEXTUAL TEACHING LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM MENYELESAIKAN SOAL CERITA PENJUMLAHAN DAN PENGURANGAN PECAHAN DI KELAS V SDN INPRES BALAROA PALU - Sukri, Mardiani (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
The Objective of this research was to obtain the description of the applying the contextual teaching learning (CTL) that can improve student learning outcomes in solving addition and subtraction word problems in V SDN Inpres Balaroa Palu. Type is a classroom action research. The design of this study refers to the research design Kemmis and Mc Taggart that is planning, action, observation, and reflection. The research results showed that the application of contextual teaching learning (CTL) that can improve student learning outcomes in solving addition and subtraction word problems berpenyebut different fractions following components, namely 1) constructivis, 2) ask, 3) finding, 4) learning community, 5) modeling, 6) reflection and 7) assessment.